The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/prot.22998
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and acid denaturation of bovine lens α‐crystallin

Abstract: The chaperone-like protein α-crystallin is a ∼35 subunit hetero-oligomer consisting of αA and αB subunits in a 3:1 molar ratio and has the function of maintaining eye lens transparency. We studied the thermal denaturation of α-crystallin by differential scanning calorimetry (DSC), circular dichroism (CD), and dynamic light scattering (DLS) as a function of pH. Our results show that between pH 7 and 10 the protein undergoes a reversible thermal transition. However, the thermodynamic parameters obtained by DSC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…This observation suggests that at 1% optimum concentration the surfactant is easily accessible to the residues which form the antiparallel β-sheet (tyrosine and proline). This was further supported by our earlier observations of acrylamide quenching studies and fluorescence spectra of released insulin and also previous reports on the same. , It may also be said that B chain residues while forming the antiparallel β-sheet at the dimer–dimer interface in hexameric insulin, if get separated from hexamer, might be acting as a nuclei for the further addition of dimeric units and propagated to amyloid fibrils. To prove that the second transition was following the aggregation DSC studies of the released insulin were carried out at different scan rates. When insulin (control) was heated at a scan rate of 10, 20, 30, 60, and 90 °C/h, with increase in the scan rate, the protein showed a shift in position of the exothermic peak to even higher temperature (Table ), i.e., the higher the scan rate is, the larger the shift in the position of exothermic peak to higher temperature .…”
Section: Results and Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This observation suggests that at 1% optimum concentration the surfactant is easily accessible to the residues which form the antiparallel β-sheet (tyrosine and proline). This was further supported by our earlier observations of acrylamide quenching studies and fluorescence spectra of released insulin and also previous reports on the same. , It may also be said that B chain residues while forming the antiparallel β-sheet at the dimer–dimer interface in hexameric insulin, if get separated from hexamer, might be acting as a nuclei for the further addition of dimeric units and propagated to amyloid fibrils. To prove that the second transition was following the aggregation DSC studies of the released insulin were carried out at different scan rates. When insulin (control) was heated at a scan rate of 10, 20, 30, 60, and 90 °C/h, with increase in the scan rate, the protein showed a shift in position of the exothermic peak to even higher temperature (Table ), i.e., the higher the scan rate is, the larger the shift in the position of exothermic peak to higher temperature .…”
Section: Results and Discussionsupporting
confidence: 72%
“…13,24 It may also be said that B chain residues while forming the antiparallel β-sheet at dimer-dimer interface in hexameric insulin, if get separated from hexamer, might be acting as a nuclei for the further addition of dimeric units and propagated to amyloid fibrils. [43][44][45] To prove that the second transition was following the aggregation DSC studies of the released insulin were carried out at different scan rates. When insulin (control) was heated at a scan rate of 10, 20, 30, 60 and 90˚C/ h, with increase in the scan rate the protein showed a shift in position of the exothermic peak to even higher temperature (Table 4), i.e., higher the scan rate is, larger the shift in the position of exothermic peak to higher temperature.…”
Section: Thermal Stability Analysismentioning
confidence: 99%
“…Acid-induced unfolding of proteins is oen incomplete and it assumes the conformations that are located between native and completely unfolded state. 44,45 The major driving force involved during acid denaturation is an intra-molecular charge repulsion, which may or may not overcome the interactions favoring the folded states such as hydrophobic forces, salt bridges and metal ion-protein interactions in case of metalloproteins. 46 The mechanism of denaturation of a given protein at low pH is proposed to be complex and may involve intricate interplay between a variety of stabilizing and destabilizing forces leading to a relatively compact structure, characteristic of the molten globule or partially unfolded intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…12,24,46 The presence of either carnosine or guanidinium does not seem to cause aggregation at the mesoscopic spatial scale typical of such a technique (see Figures S1 and S2, Supporting Information). The changes at the nanometric scale are instead investigated through the spectra collected by SAXS.…”
Section: ■ Resultsmentioning
confidence: 91%
“…4−6 The thermal behavior and chemical environment have implications for its chaperone-like function, 7−11 and are still the subject of much research. 12 −16 It has been reported that the thermal transition of α-crystallin occurs at around 60°C and varies slightly with pH, ionic strength, and the source of the protein. 12 The protein, however, was shown to retain its chaperone-like activity even above the transition temperature.…”
Section: ■ Introductionmentioning
confidence: 99%